2015
DOI: 10.1080/07294360.2015.1123230
|View full text |Cite
|
Sign up to set email alerts
|

Why do they study there? Diary research into students’ learning space choices in higher education

Abstract: Higher education learning and teaching methods have changed while most educational buildings are still rather traditional. Yet, there is an increasing interest in whether we can educate today's higher education students in yesterday's buildings. This paper aims to contribute to this debate by studying the learning space choices of higher education students in relation to their learning activities, personal characteristics and other considerations that may play a role in choosing particular learning spaces. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 20 publications
(16 reference statements)
3
46
1
1
Order By: Relevance
“…Libraries are widely used as places for preparation or revision during exams, doing assignments, meeting friends or colleagues, and completing a final dissertation (Cunningham and Walton, 2016). The emergence of the non-library category reinforces the results of previous researches (Beckers et al, 2016b;Sommer, 1970). Other studies (Beckers et al, 2016a) found catering areas, cafés, entrances, corridors, project rooms, and personal cockpits as supportive spaces.…”
Section: Library and Non-library Ilssupporting
confidence: 52%
“…Libraries are widely used as places for preparation or revision during exams, doing assignments, meeting friends or colleagues, and completing a final dissertation (Cunningham and Walton, 2016). The emergence of the non-library category reinforces the results of previous researches (Beckers et al, 2016b;Sommer, 1970). Other studies (Beckers et al, 2016a) found catering areas, cafés, entrances, corridors, project rooms, and personal cockpits as supportive spaces.…”
Section: Library and Non-library Ilssupporting
confidence: 52%
“…Personal control refers to the degree of autonomy in deciding what to do, where, and when. A diary study into higher education learning space use confirmed this desired autonomy, as students reported this aspect as one of the main reasons to study at home [57].…”
Section: The Social Dimensionmentioning
confidence: 86%
“…A diary method has also been used in several previous studies in higher education (e.g. Bakker, Vergel & Kuntze, 2015;Beckers, van der Voordt, & Dewulf, 2016;Peterson, Brown, & Jun, 2015). However, typically diary studies take place over a longer period of time, such as a week (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, typically diary studies take place over a longer period of time, such as a week (e.g. Beckers et al, 2016), or require participants to complete a diary on more than one occasion (e.g. Peterson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%